STRATEGIC PRIORITIES AND INSTRUMENTS OF THE STATE POLICY OF INFORMATIZATION OF THE ECONOMIC SYSTEM - CHASTOKOLENKO, Ihor; GRIGORENKO, Konstantin (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article focuses on modern transformational changes in the global economy, which are mainly due to the processes of digitization and informatization. The value of informatization for the economy of Ukraine is highlighted and the trends that formed positive prerequisites for the expansion of information technologies at all levels of the domestic economic system are emphasized. The analysis of the latest research and publications was carried out and a conclusion was made about the significant attention of domestic scientists to the development of the informatization of the economic system and the need for its improvement through the implementation of the appropriate state policy. The purpose of the state policy of informatization of the economic system is proposed to consider the spread of the digital communications system and digital business processes to the entire economic system of the country, the convergence of institutional, legal and economic foundations and the level of development of the digital economy sector of Ukraine and EU countries. The strategic priorities of state policy are divided in relation to the economic (digitalization of Industry 4.0 branches and ensuring the synergy of the processes of reindustrialization and digital transformation of the national economy; ensuring digital communication of the industrial production and ICT sectors, education and science, the R&D sector; inclusion of ICT sector subjects in the system of cluster structures, integration associations; strengthening cyber, information, and financial and economic security of subjects of the real sector of the economy; planning and implementation of digitalization projects strategic for the country) and organizational (building a full-fledged organizational and management system for the management of informatization of the national economic system; integration of this system into a global digital transformation management system; development of the domestic system of standardization of digital relations and communications processes; improvement of the system of state monitoring and control of the process of informatization, protection of economic and consumer rights in this market; modernization of the system of protection of intelligent digital products and services) character. Such a division was also carried out with regard to the tools of state policy: institutional, economic, financial, organizational, social, political - economic in nature; psychological, informational, resource, motivational, spatial-structural – organizational.
Keywords: informatization; state policy; economic system; national economy; strategic priorities; tools